2016
DOI: 10.3390/ijerph13090864
|View full text |Cite
|
Sign up to set email alerts
|

National and State-Specific Attitudes toward Smoke-Free Parks among U.S. Adults

Abstract: Outdoor places, such as parks, remain a source of secondhand smoke (SHS) exposure. We assessed attitudes toward smoke-free parks among U.S. adults. Data came from the 2009–2010 National Adult Tobacco Survey, a landline and cellular telephone survey of noninstitutionalized adults aged ≥18 in the 50 U.S. states and D.C. Descriptive statistics and logistic regression were used to assess the prevalence and sociodemographic correlates of attitudes toward smoke-free parks, overall and by current tobacco use. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…With the exception of current smokers’ support for government policies that limit the sale of tobacco near schools, female gender was also a consistent predictor of support for both policy types and across the smoking status continuum. This finding has been reported in other research looking at tobacco-related policy support [34,35]. Additionally, the Pew Research Center found that females are much more likely to support bigger government as compared to men, 58% and 37%, respectively [36].…”
Section: Discussionsupporting
confidence: 82%
“…With the exception of current smokers’ support for government policies that limit the sale of tobacco near schools, female gender was also a consistent predictor of support for both policy types and across the smoking status continuum. This finding has been reported in other research looking at tobacco-related policy support [34,35]. Additionally, the Pew Research Center found that females are much more likely to support bigger government as compared to men, 58% and 37%, respectively [36].…”
Section: Discussionsupporting
confidence: 82%
“…This would be consistent with findings from previous studies, which have shown that females were more likely than males to support smoke-free policies in university, 27 homes, 28,29 vehicles, 29 and outdoor spaces. 30 Moreover, an ITC study of smokers in Canada, United States, England, and Australia found that males were more likely to smoke in cars with nonsmokers than females. 31 Our results showed that the most cited reason for vaping among male vapers overall was "less harmful than cigarettes."…”
Section: Reasons For Vapingmentioning
confidence: 99%
“…Some national-level, long-running serial surveys that tracked public opinions over time were also identified in this review, with studies analysing data from the Social Climate Survey of Tobacco Control in the United States, running since 2000 [ 85 87 ]; the National Adult Tobacco Survey, run by the Centers for Disease Control and Prevention in the United States since 2009 [ 88 91 ]; and the National Drug Strategy Household Survey in Australia, running since 1995 [ 92 94 ]. Other studies used the same survey questionnaire at several points in time to measure changes in attitude and support, for example three national surveys on alcohol control attitudes of 1000 Irish adults in 2002, 2006 and 2010 [ 95 ], and a comparison of attitudes about tobacco control across two universities in the United States [ 96 ].…”
Section: Resultsmentioning
confidence: 99%